IGF-I and IGFBP-1 in Relation to Body Composition and Physical Performance in Female Olympic Athletes - Eklund, Emma; Hellberg, Anton; Berglund, Bo; Brismar, Kerstin; Hirschberg, Angelica Lindén (Frontiers in Endocrinology, 2021)
Introduction: Insulin- like growth factor-I (IGF-I) is an anabolic hormone that may affect athletic performance in female athletes, and insulin-like growth factor binding protein-1 (IGFBP-1) is an important regulator of bioactive IGF-I. There is limited knowledge of the role of endogenous IGF-I and IGFBP-1 for body composition and physical performance in female elite athletes. Purpose: To examine IGF-I, age adjusted IGF-I (IGFSD), IGFBP-1 and insulin in female Olympic athletes compared with controls and different sport categories, and in relation to body composition and physical performance in the athletes. Methods: Female athletes (n=103) and untrained controls (n=113) were included in this cross-sectional study. Body composition was established by dual-energy X-ray absorptiometry. Serum IGF-I and IGFBP-1 were analyzed by radioimmunoassay and IGFSD was calculated. Insulin was analyzed by electrochemiluminescence immunoassay. Athletes were offered to participate in standardized physical fitness tests. Results: The athletes demonstrated significantly higher IGF-I, IGFSD and IGFBP-1 and lower insulin levels than controls (p<0.05, p<0.05, p<0.01, p<0.001 respectively). Power athletes had significantly higher IGFSD compared to both endurance and technical athletes (p<0.05, p<0.01, respectively). In athletes and controls combined, significant positive correlations were found between IGF variables and higher bone mineral density (BMD) and lean mass and lower fat percent. IGF-I was positively correlated with squat jump (rs = 0.28, p<0.05) and IGFBP-1 correlated positively with squats (rs =0.35, p<0.05). Conclusion: We found higher IGF-I, IGFSD and IGFBP-1 in female athletes than controls, and the highest IGFSD in power athletes. IGF-I and IGFBP-1 were related to increased BMD and lean mass and lower fat percent, as well as were positively associated with physical fitness tests. Future studies are needed to elucidate if these results reflect adaptive responses to physical activity or genetic predisposition.